Urban Farming During the Pandemic and Its Effect on Everyday Life - Maya Andini; Ova Candra Dewi; Annisa Marwati (International Journal of Built Environment and Scientific Research, 2021)
This study aims to see the effect of practicing urban farming in limited space in landed houses, especially during this pandemic. Pandemic forces us to stay at home at all times while continuing to do our daily activities of working and studying. This results in a shifting of time consumption we used to spend time commuting to work for other activities, including urban farming at home. Urban farming is the activity of growing and producing food in the city, as food is one of the basic needs of humans to survive. In addition to supporting food security within the area, it gives benefits also to the people’s health and well-being, as well as the surrounding environment. The methods used in this study are exercising and observing the availability of space and its effect on people and living space (environment) from the literature review point of view and case studies. This study eventually finds that performing urban farming as a choice of activity is proven to be beneficial in maintaining people’s health and wellbeing.